HUBUNGAN LINGKUNGAN SEKOLAH DENGAN KEDISIPLINAN SISWA - Juli Yanti Harahap; Rosmita Ambarita (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
This study aims to determine the relationship between the school environment and student discipline in the Medan 2 MAN Model. The hypothesis proposed is the relationship between the school environment and student discipline in the MAN 2 Model Medan. The subject of the study amounted to 65 students who were selected based on the criteria needed by researchers by taking all existing populations. Data collection was done using two types of scales, namely disciplinary scale. and the scale of the school environment by giving a questionnaire to the research sample. The data analysis method used in this study is a regression test using the Pearson Product Moment formula.